2012
DOI: 10.1681/asn.2011111072
|View full text |Cite
|
Sign up to set email alerts
|

C3a and C5a Promote Renal Ischemia-Reperfusion Injury

Abstract: Renal ischemia reperfusion injury triggers complement activation, but whether and how the small proinflammatory fragments C3a and C5a contribute to the pathogenesis of this injury remains to be elucidated. Using C3aR-, C5aR-, or C3aR/C5aR-deficient mice and models of renal ischemia-reperfusion injury, we found that deficiency of either or both of these receptors protected mice from injury, but the C3aR/C5aR-and C5aR-deficient mice were most protected. Protection from injury was associated with less cellular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 47 publications
9
156
2
1
Order By: Relevance
“…Contrary to reports of intestinal IR, there is a slight improvement in disease outcomes for C3ar1 2/2 animals subjected to renal IR injury (65). In this study, the investigators demonstrated that C3a administered directly to renal tubule epithelial cells increased the production of chemotactic factors directing leukocytes to the site of injury.…”
Section: C3a In Diseasecontrasting
confidence: 63%
See 1 more Smart Citation
“…Contrary to reports of intestinal IR, there is a slight improvement in disease outcomes for C3ar1 2/2 animals subjected to renal IR injury (65). In this study, the investigators demonstrated that C3a administered directly to renal tubule epithelial cells increased the production of chemotactic factors directing leukocytes to the site of injury.…”
Section: C3a In Diseasecontrasting
confidence: 63%
“…However, although the pharmacology of SB290157 may be controversial, the conclusion drawn by the investigators could be reinterpreted to take into account the acute "antineutrophil" effects of C3aR that were discovered recently (32). It is uncontroversial that, at least at the level of the nephron, C3aR is involved in the pathogenesis of renal disease, including the induction of metaplasia in nephron epithelial cells central to the disease (65,66). These actions appear synergistic to the role of C5aR1 at the tissue level, but they may be redundant in the presence of elevated C5a concentrations, which is a more potent proinflammatory mediator than C3a, at the receptor level.…”
Section: C3a In Diseasementioning
confidence: 99%
“…Reciprocal transplant studies showed that donor kidney-derived C3 and not systemic recipient C3 is the predominant mediator of IR injury (101). Using C3aR-, C5aR-, or C3aR/C5aR-deficient mice (102), investigators observed that deficiency of either or both of these receptors protected mice from kidney IR injury and that their expression on either renal tubular epithelial cells or circulating leukocytes contributes to the pathogenesis. Together, the data indicate that IR injury upregulates production of complement components by kidney endothelial and tubular cells and infiltrating immune cells.…”
Section: Kidney-derived Complement and Diseasementioning
confidence: 99%
“…This has been suggested from reports in brain deceased donors whose raised donor CD88 expression on renal tubuloepithelial cells is associated with worse allograft function compared to living donors [43]. In addition, bone marrow chimera studies in mice deficient in C3aR and CD88 on renal tubuloepithelial cells or circulating leucocytes resulted in little IR injury in the kidney [44]. C5b-9 has also been reported to be detected in pre-implantation renal allograft biopsies of human deceased donors with none seen in live donors.…”
Section: Ischaemia-reperfusion Injurymentioning
confidence: 92%